Application Of Lean Construction Method In Cost And Time Control Of High-Rise Building Projects In Urban Areas - Harita, Hamedoni (Innovative Research in Civil and Environmental Engineering, 2025)
This study aims to explore the application of Lean Construction methods in controlling costs and time in high-rise building projects located in urban areas. Lean Construction, which focuses on reducing waste, improving workflows, and enhancing coordination, has proven to be effective in increasing project efficiency. Case studies were conducted on several high-rise projects that implemented Lean principles such as the Last Planner System (LPS), value stream mapping, and daily huddles to identify and address issues related to cost and time. The findings show that the application of Lean Construction resulted in a reduction of project costs by up to 20% and a decrease in project completion time by up to 15%. However, challenges such as resistance to change, lack of training, and the adaptation of Lean methods to the specific challenges of urban environments were identified as barriers that need to be addressed. In conclusion, Lean Construction methods offer an effective approach for managing costs and time in high-rise projects in urban areas, with success dependent on the extent to which Lean principles are comprehensively implemented.